Effect of Porphyritic Andesite Intrusion on The Formation of Contact Metamorphism Aureole in Selo Gajah Hill Clastic Limestone, Bojonegoro Regency, East Java, Indonesia - Tri Winarno; Jenian Marin; Wisnu Wijaya Jati (UIR PRESS, 2020)
At Selo Gajah Hill, Jari Village, Gondang Sub-district, Bojonegoro Regency, East Java there are limestone intruded by porphyritic andesite. The intrusion produces contact metamorphisms in the wall rocks. It is very interesting to study the protolith rock, facies of metamorphism and the zonation of contact metamorphism aureole. This research uses field observation method and laboratory analysis i.e. petrographic analysis. Field observation is conducted by doing geological mapping in the Bukit Selo Gajah area and rock sampling for petrographic analysis. Petrographic analysis aims to describe the texture of the rocks and the percentage of minerals, which will be used to determine the protolith rock, metamorphism facies and the determination of contact metamorphism zone. The lithology found in Mount Selo Gajah from oldest to youngest are clastic limestone with intercalation of marl, marl with intercalation of sandstone, porphyritic andesite intrusions, hornfels, and pyroclastic breccia. Metamorphic rocks on Selo Gajah Hill is the product of contact metamorphism of carbonate rock which was intruded by porphyritic andesite intrusion. The metamorphism facies found in the research area are hornblende hornfels and pyroxene hornfels with the protolith rock is carbonate rocks. Metamorphism zone in Selo Gajah Hill is divided into two zones: The zone closest to the intrusion body is vesuvianite zone or idiocrase zone with a radius of 40-140 m from the outer part of the intrusion body and the monticellite zone with radius ranging from 25 to 75 m from the outside of the vesuvianite zone.